Treatment of fibrillary glomerulonephritis with rituximab: a 12-month pilot study. Issue 1 (2nd July 2020) - Erickson, Stephen B; Zand, Ladan; Nasr, Samih H; Alexander, Mariam P; Leung, Nelson; Drosou, Maria Eleni; Fervenza, Fernando C
Abstract: Background: Fibrillary glomerulonephritis (FGN) is a rare type of glomerulonephritis with poor prognosis, with no known effective therapies available for treatment. The objective of the study was to evaluate the efficacy and safety of rituximab in treatment of patients with FGN and to investigate the effect of rituximab on DNAJB9 levels. Methods: This was a pilot prospective clinical trial in which patients with idiopathic FGN were treated with two courses of rituximab (1 g each) 2 weeks apart at the beginning and then again at 6 months. Primary outcome was defined as preservation of kidney function at 12 months with stable or increased creatinine clearance. Secondary outcome was defined as achieving complete remission (CR) defined as proteinuria <300 mg/24 h or partial remission (PR) with proteinuria <3 g/24 h and at least 50% reduction in the proteinuria. DNAJB9 levels were also measured in the serum at baseline, 6 and 12 months. Results: The creatinine clearance did not change significantly during this time, from 47.7 mL/min/1.73 m 2 at baseline to 43.7 mL/min/1.73 m 2 during follow-up (P = 0.15). Proteinuria declined from 4.43 (1.6–5.53) g/24 h at baseline to 1.9 (0.46–5.26) g/24 h at 12 months but did not reach significance (P = 0.06). None of the patients reached CR, and 3 of the 11 achieved PR. There was no change in the DNAJB9 levels following treatment with rituximab. The most common adverse event was nasal congestion, fatigue and muscle cramps. Conclusions: Treatment of patients with two courses of rituximab over a span of 6 months was associated with stabilization of renal function but did not result in a significant change in proteinuria and with no change in the DNAJB9 levels. Graphical Abstract: